2021
DOI: 10.1039/d1nj00293g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and theoretical calculations of metal-antibiotic chelation with thiamphenicol:in vitroDNA and HSA binding, molecular docking, and cytotoxicity studies

Abstract: Thiamphenicol (TM) is an antimicrobial drug and a methyl-sulfonyl analogue of chloramphenicol. New metal complexes of TM with Zn(II), Cu(II), Ni(II), Co(II) and Fe(II) were synthesized and characterized using elemental...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 63 publications
0
21
0
Order By: Relevance
“…The new bonds between oxidovanadium(IV) and O and N sites in all investigated compounds had average bond lengths of 1.09-2.09, which are assumed to have an ionic character of the metal to oxygen and nitrogen, respectively [25], excluding the bond length of V-O45 in the CTNZ, which showed a covalent bond character with bond length >2 Å. Moreover, the angles around the individual central vanadium ion indicated that the compounds implemented a pyramidal geometry, as presented in Table S2, Supplementary Materials.…”
Section: Optimized Molecular Geometrymentioning
confidence: 99%
“…The new bonds between oxidovanadium(IV) and O and N sites in all investigated compounds had average bond lengths of 1.09-2.09, which are assumed to have an ionic character of the metal to oxygen and nitrogen, respectively [25], excluding the bond length of V-O45 in the CTNZ, which showed a covalent bond character with bond length >2 Å. Moreover, the angles around the individual central vanadium ion indicated that the compounds implemented a pyramidal geometry, as presented in Table S2, Supplementary Materials.…”
Section: Optimized Molecular Geometrymentioning
confidence: 99%
“…The formed structure of the metal complexes is square-pyramidal geometry with negligible distortion. The bond length around the metal ion was in the range 1.95-2.60 Aº between the donating atoms and the vanadyl ion, which showed a range of small and medium ionic character (bond length > 2 Å) [41]. On the other hand, there was a direct correlation between the length of a metal-oxygen bond and its stretching frequency.…”
Section: Molecular Modeling Of Investigated Compounds 281 Geometry Descriptionmentioning
confidence: 94%
“…The extracted data from the log files showed that the vibration frequency did not have any imaginary frequencies and that the molecule was a minimum on the potential energy surface. Gauss View software was used to visualize the fchk files and extract the E LUMO and E HOMO levels and energy orbitals to estimate the essential quantum parameters using the following equations: energy gap (E gap = E LUMO − E HOMO ), absolute electronegativities (χ = −E HOMO +E LUMO /2), absolute hardness (η = E LUMO − E HOMO /2), chemical potentials (µ = −χ), global softness (S = 1/2η), and global electrophilicity (ω = π2/2η) [41].…”
Section: Molecular Modeling Methodsmentioning
confidence: 99%
“…In the current study, we used the HeLa cell line, derived from cervical cancer cells, for testing the cytotoxicity of the Cu(II) compounds. [53][54][55][56][57] All the test compounds 1-4, at a concentration of 100 ug mL À1 , were applied to HeLa cells for about 24 hours at 37 1C. Subsequently, the MTT assay was performed to determine cell viability.…”
Section: In Vitro Cytotoxicity Studiesmentioning
confidence: 99%